‘Exploring the potential of the law of delict in South Africa to address climate harms caused by private actors' - Naicker, Terysha Tiara (Department of Public Law, 2026)
This dissertation explores whether South Africa's law of delict, which allows individuals to claim damages for harm caused by the wrongful and culpable conduct of another, can evolve to address climate harms caused by private actors in the country. It does so in response to carbon-emitting companies (polluters) being identified, through advancing climate science, as primary contributors to climate change due to their sizable historic and cumulative greenhouse gas (GHG) emissions, meanwhile, marginalized and vulnerable communities with negligible emissions, particularly in the Global South, are disproportionately affected, suffering widespread climate harm that infringes many mutually reinforcing human rights and compounds existing systemic socio-economic inequalities. In South Africa, this reality threatens the Constitution's transformative goals to achieve social justice. The Constitution mandates that common law evolve in line with its transformative objectives, values, and the rights enshrined in the Bill of Rights. In light of this constitutional directive and the grave social injustices worsened by climate harm, this research explores whether delict, and its elements (damage, conduct, fault, causation, wrongfulness), can evolve to enable those most affected by climate harm to pursue claims for damages against polluters responsible for substantial historical and ongoing emissions. The research incorporates novel insights from notable foreign strategic private climate litigation concerning polluters' accountability for climate harm, including cases such as Re Greenpeace Southeast Asia, Lliuya v. RWE, Smith v Fonterra and Milieudefensie v. Royal Dutch Shell, and is framed by Murcott's theory of transformative environmental constitutionalism (TEC). Murcott explains that the transformative project's aspiration of social justice cannot be realised without implementing environmentalism, because well-functioning socio-ecological systems (dependent on a stable climate) is a pre-condition for human flourishing. Thus, TEC urges courts to embrace a socio-ecological systems perspective and justice-oriented framing of disputes concerning converging socio-ecological crises, considering how these disputes reflect intersecting social, environmental, and climate injustices to ensure that the adjudication process is responsive to the realities faced by particularly vulnerable groups and environments in the Anthropocene. Therefore, the research, adopting this framing, investigates the potential of delict to evolve along transformative constitutional lines, incorporating environmentalism through TEC, to adequately address climate harm and its underlying systemic causes and impacts, including interlocking social, environmental, and climate injustices.